Social patterning of inflammation over the lifecourse and its relationship with mortality. (13th November 2019) - Castagné, R; Chadeau-Hyam, M; Karimi, M; Stringhini, S; Vineis, P; Delpierre, C; Kelly-Irving, M
Abstract: Background: This study explores (i) the relationship between socioeconomic position (SEP) across the life course and circulating C-reactive protein (CRP), a marker of systemic inflammation, in 6 European cohort studies (in up to N = 23 008) participating in the Lifepath project and (ii) interrogate the hypothesis of a cumulative biological risk (allostatic load, AL) reflecting 4 physiological systems, including inflammation, potentially predicting future risk of death in one of the cohort. Methods: First, we estimated the association between measures of three time point SEP and adulthood CRP, adjusting for health behaviours and body mass index (BMI). To mimic life course experiences, we sequentially adjusted for the chronologically ordered measures of SEP. Next we used mortality data from the 1958 British birth cohort to operationalise AL from 14 biomarkers collected at age 44. Multivariate Cox proportional hazards regression was used to estimate hazard ratios for the association between AL, biological sub-scores and individual biomarkers with mortality. Results: Educational attainment was most strongly related to inflammation where low educational attainment was associated with higher log-transformed levels of CRP (β = 0.30, (0.22-0.38)). Higher AL at 44 years old was a significant predictor of mortality 11 years later (HR = 3.56 (2.3 to 5.53)). Among the four physiological systems, only the immune-inflammatory and cardiovascular sub-scores were significantly related to mortality. Conclusions: Socioeconomic circumstances across the life course are associated with higher levels of inflammation in adulthood which in turn predict subsequent risk of death. But our findings also suggest that the cumulative AL measure consisting of all the biomarkers was a better measure for predicting death adding evidence on the biological embodiment in response to chronic stress, suggesting that social-to-biological processes are at play, beyond the impact of health behaviours and BMI.